2020
DOI: 10.2196/21703
|View full text |Cite
|
Sign up to set email alerts
|

Using Smartphone Sensor Data to Assess Inhibitory Control in the Wild: Longitudinal Study

Abstract: Background Inhibitory control, or inhibition, is one of the core executive functions of humans. It contributes to our attention, performance, and physical and mental well-being. Our inhibitory control is modulated by various factors and therefore fluctuates over time. Being able to continuously and unobtrusively assess our inhibitory control and understand the mediating factors may allow us to design intelligent systems that help manage our inhibitory control and ultimately our well-being. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 70 publications
0
9
0
Order By: Relevance
“…If this were the case, existing interventions could be adapted to focus more on these cognitive functions. In the light of the findings of the present study, it would be advisable in such future studies to use self-report measures or, for example, ecological momentary assessment [ 52 54 ] in addition to objective perfomance based measures of cognitive flexibility and central coherence in a single situation in the lab.…”
Section: Discussionmentioning
confidence: 99%
“…If this were the case, existing interventions could be adapted to focus more on these cognitive functions. In the light of the findings of the present study, it would be advisable in such future studies to use self-report measures or, for example, ecological momentary assessment [ 52 54 ] in addition to objective perfomance based measures of cognitive flexibility and central coherence in a single situation in the lab.…”
Section: Discussionmentioning
confidence: 99%
“…Note that if sleep is continuous, the Fitbit may record one long multi-hour sleep cycle, but these cycles are usually broken-up by short wake cycles when someone moves while lying down or becomes restless. [2,92], we required participants to have a minimum number of hours of data collected for training prediction models. We filtered out study participants that did not have at least 100 total hours of data prior to the internship starting, and during the internship year.…”
Section: 44mentioning
confidence: 99%
“…Multitask learning (MTL) is a machine learning technique used to train separate, but related prediction tasks together [13]. Previous work [88,92] using mobile sensing data to predict mental health [88], the models had input "shared layers" where neural network parameters were shared across tasks, and output "single-task" layers, where parameters were specific to each task:…”
Section: Multitaskmentioning
confidence: 99%
See 1 more Smart Citation
“…These data sources offer valuable behavior and health features. For example, Tseng et al [ 15 ] found that they could predict a person’s inhibitory control based solely on phone usage statistics. To enable longitudinal data collection without additional hardware and participant involvement, we do not incorporate these additional wearable information sources into the analysis.…”
Section: Related Workmentioning
confidence: 99%